Molecular ecology of introduced species in South Africa : the bud gall-forming wasp Trichilogaster acaciaelongifoliae and the Argentine ant Linepithema humile - Lado, Thomas Francis (Stellenbosch : Stellenbsoch University, 2008)
Thesis (PhD)--Stellenbosch University, 2008.